Examining customer satisfaction on implementation of corporate social responsibility on Malaysian Islamic banking - Abdul Hapzis, Amira Nur Raeha; Tahir, Nor Suziwana (2023)
The value of Corporate Social Responsibility (CSR) is recognized as an integral part of the organizations because implementing CSR activities assists businesses develop strong reputations, secure their business activities, and maximize earnings that can be reinvested into the community. In the banking industry, CSR is not new, and it promotes a positive corporate image, engages employees, and assures customers satisfaction by incorporating moral concepts into banking activities. It is undeniable that CSR ensures banks’ financial soundness and sustainable profitability as it upholds compliance with ethical and sustainability standards, transparency of products and reliability of financial disclosures. Carroll’s CSR dimensions postulate four-part definition of CSR which are economic, legal, ethical, and discretionary (philanthropic) expectations that society has of organizations at a given point in time. Hence, this study aims to examine the impact of these four dimensions on customer satisfaction. 400 customers of Malaysian Islamic Banking in Peninsular Malaysia answered the survey. The questionnaires comprised of six sections and the respondents were chosen by using stratified sampling technique. The instruments were adopted and adapted from past literature and were tested for reliability and normality. The data were further analyzed by using Descriptive Analysis, Reliability Analysis, Normality testing and Multiple Regression Analysis to answer the research questions. The findings demonstrate that all four CSR dimensions have significant relationship with the customer satisfaction of Malaysian Islamic Banking. In addition, the main dimension of CSR that influence customer satisfaction towards Malaysian Islamic Banking is ethical responsibility. The findings of this study are crucial to increase the understanding of the banking customers towards CSR and provide guideline for the Islamic banks in Malaysia on how to strengthen their CSR practices to enhance their corporate image and increase transparency. This study fits with the Theory of Stakeholder because CSR activities create some responsibility for the Islamic Bank to serve this country according to shariah compliance which is relay relevant, accurate and reliable information to the stakeholders.